(untitled) (Research Announcements "Heritage BG", 2025)
We can trace, through the artistic worlds created by the writers between 1950 and 1989, the way in which critics perceived Children`s and Young Adult science fiction - from the instrumental of ideological education of the younger generation to a tool provoking the reader’s imagination to think about the present, its real problems and perspectives which would have an effect on the future. On the one hand, the construction of a literary-historical background ofthe period is important. It traces the ways in which the new system channels the cognitive and educational function of science fiction; the ideological problems of the time, modeled by the political, socialtransformations. Onthe otherhand, it creates conditions of a different ideological environment which creates not just alternativeness, but freedom for a critical interpretation of contemporary world. References: Primary Sources: Atanasov, Z. (1955). Detskata literatura i zadachite na komunist-icheskoto vazpitanie. – Septemvri, 11, 155–162. Antonov, N. (1960). Chudnoto pateshestvie. Sofia. Georgiev, A. (1974). Poletat kam Purpurnia drakon. Plovdiv. Dilov, L. (1980). Zvezdnite priklyuchenia na Numi i Niki. Sofia. Dilov, L. (1983). Do rayskata planeta i nazad. Sofia. Kolarova, E. (1987). Shte ima li promyana? – ABV, 22 septemvri, s. 5. Lizhev, T. (1976). Gradinite na Mars. Varna. Miltenov, Y. (1968). Chiponosko na Lunata. Sofia. Slavov, A. (1965). Faktorat „X“. Sofia. Selyanov, V. (1964). Trevoga v Kosmosa. Sofia. Ukaz 172 (2000). Zakon za detskata literatura. In: Balgarskata detska literatura (antologia). Sofia, 430–431. Ukaz 123 (2000). Zakon za detskata i mladezhka knizhnina. In: Balgarskata detska literatura (antologia). Sofia, 432–437. Ukaz 150 (1946). Zakon za izmenenie i dopalnenie na Zakona za detskata i mladezhka knizhnina. – Darzhaven vestnik, 209, 13 septemvri. Ukaz 181 (1946). Pravilnik za prilagane na zakona za detska i mladezhka knizhnina. – Darzhaven vestnik, 275, 29 noemvri. Secondary Sources: Angelov, D. (1956). Zemyata pred gibel. Sofia. Ivanov, S. (1950). Fantastika i deystvitelnosty. – http://www.fandom.ru/about_fan/ivanovs_1.htm Konstantinova, E. (1987). Vaobrazhaemo i realno: Fantastikata v balgarskata hudozhestvena proza. Sofia. Konstantinova, E. (1986). Sporovete okolo fantastikata. – ABV, 29 may, s. 4. Milchev, A. (1986). Trudnata sadba na fantastikata. – Literaturen front, 13 fevruari, s. 2. Svetlinov, B. (1955). Edin den na Lunata. Sofia. Stapov, P. (1965). Gosti ot Mion. Sofia. Umlenski, I. (1951). Tezisi po detska literatura. Sofia.